TANGGUNG JAWAB HUKUM LEMBAGA KUSTODIAN TERHADAP INVESTOR REKSA DANA - NIM. A1011211185, ALYA PUTRI RAMADHANTY (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The purpose of this study is to find out and explain how accountability is for violations committed by Custodian Institutions in mutual fund investments as well as explaining the duties and functions of Custodian Institutions as a place to store funds for mutual fund investors.This research is normative legal research in which this legal research examines and analyzes statutory regulations, legal principles and legal norms which will be applied as rules or norms which are a benchmark for humans to behave appropriately by studying the applicable legal provisions. The data obtained in this research was through library research and then analyzed descriptively.The results of this research indicate that regarding the responsibilities of Custodian Institutions towards investors in terms of the Capital Markets Law, Custodian Institutions based on the provisions of Article 46 UUPM have given investors the right to demand compensation if the Custodian Institution makes a mistake, whether intentionally, negligently or lack of caution. . As well as the protection of mutual fund investors which has been regulated in the Financial Services Authority regulations regarding mutual funds. It aims to provide insight into the legal responsibilities and legal protection that investors can expect when engaging in transactions in the capital markets.Keywords : Custodian, Investor Protection, Mutual Funds Abstrak Penelitian ini bertujuan untuk mengetahui dan menjelaskan bagaimana pertanggungjawaban terhadap pelanggaran yang dilakukan oleh Lembaga Kustodian dalam investasi reksa dana serta menjelaskan tugas dan fungsi dari Lembaga Kustodian sebagai tempat penyimpanan dana bagi para investor reksa dana.Penelitian ini merupakan penelitian hukum normatif yang dimana penelitian hukum ini mengkaji dan menganalisis peraturan perundang-undangan, asas-asas hukum, dan norma-norma hukum yang akan diaplikasikan sebagai kaidah atau norma yang merupakan patokan manusia untuk berperilaku yang sewajarnya dengan mengkaji ketentuan hukum yang berlaku. Data yang diperoleh dalam penelitian ini yaitu melalui penelitian kepustakaan kemudian dianalisis secara deskriptif.Hasil penelitian ini menunjukkan bahwa terkait tanggung jawab Lembaga Kustodian terhadap investor ditinjau dari Undang-Undang Pasar Modal maka Lembaga Kustodian berdasarkan ketentuan Pasal 46 UUPM telah meletakkan hak kepada investor untuk menuntut ganti rugi apabila Lembaga Kustodian melakukan kesalahan baik sengaja, kelalaian maupun kurang kehati-hatian. Serta perlindungan investor reksa dana yang telah diatur dalam peraturan-peraturan Otoritas Jasa Keuangan terkait reksa dana. Ini bertujuan untuk memberikan wawasan tentang tanggung jawab hukum dan perlindungan hukum yang dapat diharapkan investor ketika terlibat dalam transaksi di pasar modal.Kata Kunci : Kustodian, Perlindungan Investor, Reksa Dana